IMPLEMENTATION OF THE AR-RASYID METHOD IN MEMORIZING THE QUR'AN AT THE HOUSE OF TAHFIDZUL QUR'AN AL-HIJAZ, KLATEN DISTRICT, 2023 - Alsha inayah diniary; Nurul Latifatul Inayati (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
Memorizing the Qur'an becomes easy when finding a suitable method to facilitate the memorization process. This study aims to describe the method memorization method used in the house of tahfidzul qur'an al-hijaz namely ar-Rasyid method as well as the supporting and inhibiting factors in the implementation of the method. the method. This research uses qualitative research with phenomenological type. The research subjects are santri Ali and utsman classes. The data collection method uses observation, interviews, and documentation. Data analysis techniques using interactive analysis analysis which includes data condensation, data presentation, and conclusion drawing. conclusion. The results showed that the ar-Rashid method is a combination of the sima'I and talaqqi methods. a combination of the sima'I and talaqqi methods, namely the students add new memorization by listening to the audio murottal given by the teacher and then memorizing the audio murottal given by the teacher. by listening to the murottal audio given by the teacher then repeating the verses and talaqqi. repeating verses and depositing directly to the ustadz to be corrected directly. corrected directly. The supporting factors are easy methods, the existence of experienced teachers and motivation from students and parents. While the inhibiting factors are that there are still students who are less fluent in reading the in reading the Qur'an, the absence of students and less organized time management. time management is less organized.